The Impact Of Profitability And Solvency On Firm Value Coal Mining Subsector Businesses Listed On The Stock Exchange Of Indonesia 2020–2024 - Uswatun Hasanah; Siti Hasbiah; Paramaswary Aslam (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
Coal mining firms listed on the Indonesia Stock Exchange (IDX) are the subject of this study between 2020 and 2024. These Businesses have a very important part in the national economy but simultaneously face difficulties like price volatility, shifts in global demand, and renewable energy transition policies. The study is motivated by previous various research results regarding impact of solvency and profitability on company value, necessitating further empirical examination. This study's objective is to evaluate the impact of profitability and solvency on company value. A quantitative causal-associative approach was employed using panel data from eight businesses that consistently release yearly reports throughout the study period, generating 40 observations. Analysis of multiple linear regression was performed on the data using SPSS version 30. The findings reveal that profitability, represented by Return on Assets (ROA), has a negative yet insignificant impact on firm value as measured by Price to Book Value (PBV). Conversely, solvency, proxied by Debt to Equity Ratio (DER), demonstrates a beneficial and noteworthy impact on the company's value. Collectively, profitability and solvency explain 20.3% of firm value variation. These results underscore the importance of maintaining a balanced capital structure to enhance investor confidence and corporate valuation. Academically, this research enriches financial management literature within the energy sector, while practically offering insights for managers and investors in financial decision-making.